Association of Use of Tourniquets During Total Knee Arthroplasty in the Elderly Patients With Post-operative Pain and Return to Function - Jian Zhao; Jian Zhao; Xin Dong; Ziru Zhang; Quanyou Gao; Yunfei Zhang; Junlei Song; Shun Niu; Tian Li; Jiying Chen; Fei-Long Wei (Frontiers Media S.A., 2022)
ObjectiveDuring total knee arthroplasty (TKA), tourniquet may negatively impact post-operative functional recovery. This study aimed at investigating the effects of tourniquet on pain and return to function.MethodsPubmed, Embase, and Cochrane Library were comprehensively searched for randomized controlled trials (RCTs) published up to February 15th, 2020. Search terms included; total knee arthroplasty, tourniquet, and randomized controlled trial. RCTs evaluating the efficacies of tourniquet during and after operation were selected. Two reviewers independently extracted the data. Effect estimates with 95% CIs were pooled using the random-effects model. Dichotomous data were calculated as relative risks (RR) with 95% confidence intervals (CI). Mean differences (MD) with 95% CI were used to measure the impact of consecutive results. Primary outcomes were the range of motion (ROM) and visual analog scale (VAS) pain scores.ResultsThirty-three RCTs involving a total of 2,393 patients were included in this study. The mean age is 65.58 years old. Compared to no tourniquet group, the use of a tourniquet resulted in suppressed ROM on the 3rd post-operative day [MD, −4.67; (95% CI, −8.00 to −1.35)] and the 1st post-operative month [MD, −3.18; (95% CI, −5.92 to −0.44)]. Pain increased significantly when using tourniquets on the third day after surgery [MD, 0.39; (95% CI, −0.19 to 0.59)]. Moreover, tourniquets can reduce intra-operative blood loss [MD, −127.67; (95% CI, −186.83 to −68.50)], shorter operation time [MD, −3.73; (95% CI, −5.98 to −1.48)], lower transfusion rate [RR, 0.85; (95% CI, 0.73-1.00)], higher superficial wound infection rates RR, 2.43; [(5% CI, 1.04-5.67)] and higher all complication rates [RR, 1.98; (95% CI, 1.22-3.22)].ConclusionModerate certainty evidence shows that the use of a tourniquet was associated with an increased risk of higher superficial wound infection rates and all complication rates. Therefore, the findings did not support the routine use of a tourniquet during TKA.